2006
DOI: 10.1073/pnas.0608709103
|View full text |Cite
|
Sign up to set email alerts
|

H2AX chromatin structures and their response to DNA damage revealed by 4Pi microscopy

Abstract: DNA double-strand breaks (DSBs) caused by cellular exposure to genotoxic agents or produced by inherent metabolic processes initiate a rapid and highly coordinated series of molecular events resulting in DNA damage signaling and repair. Phosphorylation of histone H2AX to form ␥-H2AX is one of the earliest of these events and is important for coordination of signaling and repair activities. An intriguing aspect of H2AX phosphorylation is that ␥-H2AX spreads a limited distance up to 1-2 Mbp from the site of a DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 31 publications
(46 reference statements)
6
81
0
1
Order By: Relevance
“…S7). This is likely a result of the endogenous cellular amplification as the phosphorylation of H2AX spreads extensively around a site of DNA breakage while TUNEL directly labels a single DNA break (32,33). High-content immunofluorescence quantitation of H2AXP levels showed clear enrichment after 12 h of doxycycline treatment over the vehicle control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S7). This is likely a result of the endogenous cellular amplification as the phosphorylation of H2AX spreads extensively around a site of DNA breakage while TUNEL directly labels a single DNA break (32,33). High-content immunofluorescence quantitation of H2AXP levels showed clear enrichment after 12 h of doxycycline treatment over the vehicle control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen and nitrogen species are potent inducers of oxidative DNA damage. To assess accumulation of cells experiencing nuclear DNA damage in the vicinity of the MTB-infected macrophages, we stained TB lesions with antibodies specific for phosphorylated g-histone2AX, whose appearance in the nuclei indicates doublestranded DNA breaks (Bewersdorf et al, 2006;Nussenzweig and Paull, 2006). The g-H2AX staining showed that abundant punctated nuclear staining of non-infected cells surrounded the MTB-infected macrophages.…”
Section: Chronic Mtb Infection Causes Squamous Cell Carcinomamentioning
confidence: 99%
“…The (53) provides an explanation for the gaps between individual gH2AX subfoci and the H2AX clusters observed with 4Pi microscopy (48).…”
Section: Focus Structure and Implicationsmentioning
confidence: 99%